A case report of acute Sheehan syndrome with a review of 29 existing reports from 1990 to 2024: is it still considered a rare disease? - Jeon, Chulhyo; Sung, Kiyoung; Cho, Jinbeom (Frontiers in Surgery, 2025)
BackgroundSheehan's syndrome (SS) can occur as a consequence of massive postpartum hemorrhage (PPH). Although traditionally considered rare, acute SS may be underestimated, especially in resource-limited settings, where even minor obstetric complications other than the commonly recognized uterine atony could lead to significant clinical consequences.Case reportA 32-year-old pregnant woman (gravida 1, para 0) at 37 weeks and 6 days of gestation developed massive PPH complicated by hemorrhagic shock, cardiac arrest, and an emergent hysterectomy, with an estimated blood loss of 20 L. Despite initial stabilization, the patient experienced acute delirium and hyperpyrexia on postpartum day 9. Urgent brain magnetic resonance imaging (MRI) and hormonal studies revealed acute necrosis of the anterior pituitary gland accompanied by multiple endocrine abnormalities. Empirical dexamethasone therapy, initially administered due to clinical suspicion of bacterial meningitis before hormonal study results became available, fortunately resulted in rapid clinical improvement. Although the exact mechanism remains unclear, steroid therapy was successfully tapered and discontinued during hospitalization, allowing the patient to be discharged without ongoing hormonal replacement therapy. Follow-up care revealed continued recovery, with partial empty sella observed on MRI 31months postpartum as a sequela of SS.ConclusionAcute SS may be underrecognized clinically, suggesting a higher incidence than previously reported. Immediate hormonal replacement might be crucial when acute SS is clinically suspected, given the delays in confirmatory testing. Careful monitoring of postpartum patients exhibiting an unusual clinical course should be implemented, as it may facilitate the early detection of potentially life-threatening complications such as adrenal crisis or acute endocrine dysfunction.